Structural and Thermal Properties of Chemically Modified Luffa Cylindrica Fibers. Issue 7 (3rd July 2021) - Premalatha, N.; Saravanakumar, S.S.; Sanjay, M R; Siengchin, Suchart; Khan, Anish
ABSTRACT: This present investigation is aimed at understanding the impact of various chemical treatments on the physicochemical properties of Luffa cylindrica fibers (LCFs). One of the major disadvantages of natural fiber as reinforcement materials in polymer composites is the incompatibility of hydrophilic nature of natural fiber and hydrophobic nature of polymers. So in this investigation, LCFs were pre-treated using optimal alkali solution followed by individual treatments with potassium permanganate, benzoyl peroxide and stearic acid to reduce the hydrophobic nature of LCF to use as reinforcement materials in composites which can be used for semi-structural applications such as household products, construction and building materials, car-interior components, etc. Further, the physicochemical properties of chemically modified LCFs were studied using thermogravimetric analysis (TGA) and X-ray diffraction (XRD). It was noticed that all modified LCFs improved crystallinity and thermal stability. Moreover, the stearic acid treatment promoted the superior thermal stability of LCFs.